Understanding Design Thinking, Lean, and Agile - Schneider, Jonny (O'Reilly Media, Inc., 2017)
Highly touted methodologies, such as Agile, Lean, and Design Thinking, leave many organizations bamboozled by an unprecedented array of processes, tools, and methods for digital product development. Many teams meet their peril trying to make sense of these options. How do the methods fit together to achieve the right outcome? What's the best approach for your circumstances? In this insightful report, Jonny Schneider from ThoughtWorks shows you how to diagnose your situation, understand where you need more insight to move forward, and then choose from a range of tactics that can move your team closer to clarity. Blindly applying any model, framework, or method seldom delivers the desired result. Agile began as a better answer for delivering software. Lean focuses on product success. And Design Thinking is an approach for exploring opportunities and problems to solve. This report shows you how to evaluate your situation before committing to one, two, or all three of these techniques. Understand how design thinking, the lean movement, and agile software development can make a difference Define your beliefs and assumptions as well as your strategy Diagnose the current condition and explore possible futures Decide what to learn, and how to learn it, through fast research and experimentation Decentralize decisions with purpose-driven, collaborative teams Prioritize and measure value by responding to customer demand